A Theory on Media Bias and Elections - Junze Sun; Arthur Schram; Randolph Sloof (Tinbergen Institute, 2019)
We develop a tractable theory to study the impact of biased media on election outcomes, voter turnout and welfare. News released by media allows voters to infer the relative appeal of the two candidates, and the closeness of elections. In large elections, the former determines the election outcome, whereas the latter drives voter turnout. With a single media outlet, a rise in media bias affects the election outcome in a non-monotonic way, and reduces voter welfare by decreasing the probability of electing the efficient candidate and increasing aggregate turnout costs. Introducing extra media outlets can systematically shift the election outcome and voter turnout in either direction, but it weakly improves voter welfare. The impact of other ways to strengthen media competition – such as increased polarization and prevention of collusion – critically depends on whether media have commitment power; if not, they can worsen information transmission and voter welfare.
Keywords: D72; D82; D83; 330; media bias; voting; Poisson games; media competition; commitment